Thrombotic Lesion of the Pulmonary Vessels in Patients with Pulmonary Embolism - A. A. Klimenko; N. A. Demidova; N. A. Shostak; M. O. Anischenko (Столичная издательская компания, 2020)
After suffering pulmonary embolism (PE), doctors are confronted with various consequences of the disease, from asymptomatic residual pulmonary thrombosis to the formation of chronic thromboembolic pulmonary hypertension (CTEPH). There is also a subgroup of patients who have undergone pulmonary embolism, who experience shortness of breath during physical exertion, absent before pulmonary embolism, or shortened dyspnea preceding PE, combined with residual thrombosis of pulmonary artery (PA) and normal average pressure in PA at rest during catheterization of the right heart (CRH). This condition is defined as chronic thromboembolic pulmonary disease or post thromboembolic syndrome. Pathogenetic aspects of this condition are not fully investigated. It is important to predict the development of postembolic syndrome and to develop algorithms for the diagnosis, treatment and rehabilitation of patients with symptoms and residual pulmonary thrombosis. In case of the development of pulmonary vasculopathy in some patients who have undergone pulmonary embolism, a severe life-threatening condition forms - CTEPH, characterized by an increase in pressure in the pulmonary artery, right heart failure due to the presence of organized blood clots that have entered the pulmonary vascular bed during PE. The volume of thrombotic masses does not always correlate with clinical symptoms, which indicates the importance of microvascular remodeling. If CTEPH is suspected, a diagnostic algorithm is required, including ventilation-perfusion scintigraphy, CT angiopulmonography and catheterization of the right heart. Treating a patient with CTEPH is a difficult task fora doctor. The timely referral of the patient to the center where they are involved in treatment, including surgery and CTEPH is extremely important. Timely performed thrombendarterectomy in some cases allows to completely cure the patient. In the case of inoperable CTEPH or residual pulmonary hypertension after thrombendarterectomy, balloon angioplasty of the PA is used as well as drug treatment with specific drugs that reduce the pressure in the PA (riociguat), endothelin receptor antagonists (bosentan, macitentan), prostanoids (inhalant illoprost) phosphodiesterase-5 inhibitor and combined therapy. In this article we considered some consequences directly related to PE: asymptomatic residual pulmonary thrombosis, chronic thromboembolic pulmonary disease, chronic thromboembolic pulmonary hypertension.